Inovasi Guru PAI dan Implikasinya Terhadap Kemampuan Creative Thinking Skill Peserta Didik - Laverdho, M. Royhan (Universitas Majalengka, 2024)
This research is motivated by the fact that students' creative thinking abilities in the PAI learning process in the subject of corpse management, advising each other in Islam are still low, this is indicated by the students' level of analysis being lacking, students have not been able to produce many ideas or answers, the ability Having very broad ideas is still lacking, even though in the learning process several innovations such as models, methods and supporting learning tools have been used in the learning process. This research is field research (Field Research) which is descriptive qualitative in nature. The subjects of this research are the Headmaster, Mr/Mrs, and the students. Data collection techniques through observation, interviews and documentation. The results of this research that we want to know are about innovation in the PAI learning process and the creative thinking abilities of students at SMA N 4 Rejang Lebong.